2012
DOI: 10.1128/mcb.00204-12
|View full text |Cite
|
Sign up to set email alerts
|

Histone Methyltransferase NSD2/MMSET Mediates Constitutive NF-κB Signaling for Cancer Cell Proliferation, Survival, and Tumor Growth via a Feed-Forward Loop

Abstract: Constitutive NF-B activation by proinflammatory cytokines plays a major role in cancer progression. However, the underlying mechanism is still unclear. We report here that histone methyltransferase NSD2 (also known as MMSET or WHSC1), a target of bromodomain protein ANCCA/ATAD2, acts as a strong coactivator of NF-B by directly interacting with NF-B for activation of target genes, including those for interleukin-6 (IL-6), IL-8, vascular endothelial growth factor A (VEGFA), cyclin D, Bcl-2, and survivin, in cast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
143
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(145 citation statements)
references
References 66 publications
1
143
0
1
Order By: Relevance
“…In prostate cancer for example, the EZH2/NSD2 axis confers increased cell proliferation, migration, invasion, stem cell-like properties and tumor growth in a mouse xenograft model [66]. Further studies in prostate cancer have shown that NSD2 acts as a co-activator with NF-κB and androgen receptor [67,68], and regulates the epithelial to mesenchymal transition by dimethylating H3K36 at the TWIST1 locus and activating TWIST1 expression [69].NSD3: frequently overexpressed in diverse tumor types NSD3, also known as WHSC1L1, is overexpressed in cancer [70] and catalyzes mono-and di-methylation at H3K36 in vitro [71]. In cells NSD3 functions as a transcriptional activator, but NSD3's KMTase activity may contribute only partially to its geneactivating role.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In prostate cancer for example, the EZH2/NSD2 axis confers increased cell proliferation, migration, invasion, stem cell-like properties and tumor growth in a mouse xenograft model [66]. Further studies in prostate cancer have shown that NSD2 acts as a co-activator with NF-κB and androgen receptor [67,68], and regulates the epithelial to mesenchymal transition by dimethylating H3K36 at the TWIST1 locus and activating TWIST1 expression [69].NSD3: frequently overexpressed in diverse tumor types NSD3, also known as WHSC1L1, is overexpressed in cancer [70] and catalyzes mono-and di-methylation at H3K36 in vitro [71]. In cells NSD3 functions as a transcriptional activator, but NSD3's KMTase activity may contribute only partially to its geneactivating role.…”
mentioning
confidence: 99%
“…In prostate cancer for example, the EZH2/NSD2 axis confers increased cell proliferation, migration, invasion, stem cell-like properties and tumor growth in a mouse xenograft model [66]. Further studies in prostate cancer have shown that NSD2 acts as a co-activator with NF-κB and androgen receptor [67,68], and regulates the epithelial to mesenchymal transition by dimethylating H3K36 at the TWIST1 locus and activating TWIST1 expression [69].…”
mentioning
confidence: 99%
“…ChIP was performed essentially as described previously 54 with the following modifications. The crude chromatin solutions were first cleared with protein A beads (Invitrogen, Carlsbad, CA, USA) that had been pre-coated with normal IgG for 2 h at 4°C, and then incubated at 4°C overnight with specific antibodies (Supplementary Table 3) before precipitation with protein A beads that had been pre-blocked with BSA and sonicated salmon sperm DNA.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was isolated and the cDNA was prepared, amplified and detected in the presence of SYBR as previously. 54 The fluorescent values were collected and a melting curve analysis was performed. Fold difference was calculated as described previously.…”
Section: Methodsmentioning
confidence: 99%
“…Histone lysine methyltransferases (HMTases) are transcriptional coregulators that target specific lysines on histones H3 and H4, and can transfer up to three methyl groups (Kme1, Kme2, and Kme3) [1]. However, the molecular mechanisms of histone mark recognition remain unclear [2][3][4][5][6]. Epigenetic marks on H3K4, H3K9, H3K27, H3K36, H3K79, and H4K20 have been reported to play primary roles in regulating the chromatin and contribute to the histone code that is still obscure [7].…”
Section: Introductionmentioning
confidence: 99%